Comparing sectoral international trade networks - Luca De Benedictis; Lucia Tajoli (Aussenwirtschaft, 2010)
This paper uses the tools of network analysis to assess the different characteristics of world trade in different manufacturing industries.The structure of the trade networks is compared to understand to what extent the world market characteristics differ between sectors. We find that in some sectors the structure of trade flows gives rise to a dense, widespread network withmany links, while in others we observe a centered network, organized around hubs that centrally coordinate the flows.The results indicate a pattern of network structures, showing a positive correlation between the goods' complexity and the network complexity, changing the extent of the relevant market and its structure across goods.
Keywords: C02; F10; F14; 330